1965
DOI: 10.1042/bj0970820
|View full text |Cite
|
Sign up to set email alerts
|

The immunochemistry of Salmonella chemotype VI O-antigens. The structure of oligosaccharides from Salmonella group U (o 43) lipopolysaccharides

Abstract: 1. A series of oligosaccharides was isolated from Salmonella milwaukee lipopolysaccharide by partial acid hydrolysis. 2. Structural studies on these oligosaccharides indicated that the O-specific side chain of this lipopolysaccharide has a repeating pentasaccharide unit that is probably alpha-d-galactosyl-(1-->3)-beta-d-galactosyl- (1-->3)-N-acetylgalactosaminyl-(1-->3)-N-acetyl- d-glucosaminyl-(1-->4)-l-fucose. 3. Another oligosaccharide, which is not structurally related to the repeating pentasaccharide unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 4 publications
1
21
0
Order By: Relevance
“…Today, one can look back at the work of these pioneers in LPS chemistry and biology [185][186][187][188][189] with a great deal of respect and admiration. Although these studies on the pyrogenicity of LPS were primarily conducted in rabbits and sheep, 190,191 pioneers such as Sheldon Wolff and Sheldon Greisman used human subjects, mostly volunteers, to investigate the human febrile responses to intravenously injected LPS in humans.…”
Section: Pioneers In the Chemistry And Pyrogenicity Of Lpsmentioning
confidence: 99%
“…Today, one can look back at the work of these pioneers in LPS chemistry and biology [185][186][187][188][189] with a great deal of respect and admiration. Although these studies on the pyrogenicity of LPS were primarily conducted in rabbits and sheep, 190,191 pioneers such as Sheldon Wolff and Sheldon Greisman used human subjects, mostly volunteers, to investigate the human febrile responses to intravenously injected LPS in humans.…”
Section: Pioneers In the Chemistry And Pyrogenicity Of Lpsmentioning
confidence: 99%
“…These enterobacteria may, thus, serve as an antigenic reservoir, continuously stimulating anti-Gal production. Structure analysis of carbohydrates in LPS of enterobacteria have demonstrated oligosaccharides with terminal e-galactosyl residues (termed e-galactosyl-like epitopes) on bacteria such as Salmonella [59], Klebsiella [9,15], E. coli [49,50] and Clostridia [43]. These epitopes contain galactosyl or glucosyl penultimate to the terminal e-galactosyl residues and are structurally different from the e-galactosyl epitope which has not been found in bacteria.…”
Section: Anti-gal and Infectious Agentsmentioning
confidence: 99%
“…However, the contemporaneous production of anti-Gal in humans, anthropoid apes, and Old World monkeys probably represents an ongoing immune response to Galal-+3Gal structures found on various gastrointestinal bacteria, including Salmonella, Klebsiella, and Escherichia coli (16)(17)(18). Our studies have indeed demonstrated a specific in vitro interaction of purified anti-Gal with these bacterial strains (unpublished data).…”
Section: Discussionmentioning
confidence: 99%